Pengaruh Paritas, Jarak Kehamilan, Usia pada Kehamilan dengan Preeklamsia di Puskesmas Adiarsa Karawang - Nurjanah, Annisa Amalia; Sutarno, Maryati (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT According to data from the World Health Organization (WHO) in 2020, it is estimated that every day there are 934 cases of preeclampsia occurring throughout the world. Around 342,000 pregnant women experience preeclampsia. Based on a preliminary study at the Adiarsa Karawang Community Health Center, data on preeclampsia cases in 2022 was 14.57%, in 2023 it was 10.0%. This study aims to determine the effect of parity, gestational spacing, and maternal age on pregnancies with preeclampsia at the Adiarsa Karawang Community Health Center. This type of quantitative research, analytical survey research design with a cross sectional approach was carried out at the Adiarsa Community Health Center, Karawang Regency in June-July 2024. Population in this study were all pregnant women who experienced preeclampsia totaling 110 people. The sample in this study was 53 with a purposive sampling technique used. Data collection uses secondary data taken from patient register records. Data analysis was univariate (frequency distribution) and bivariate (chi square). It is known that of the 53 pregnant women at the Adiarsa Karawang Community Health Center in 2024, 39 (73.6%) experienced preeclampsia and 14 (26.4%) did not experience preeclampsia. 42 (79.2%) with at-risk parity (≥ 4) and 11 (20.8%) with no-risk parity. 37 (69.8%) with risky pregnancy intervals (≤ 2 years) and 11 (20.8%) with no risky pregnancy intervals. 37 (69.8%) were at risk (≤ 20-≥ 35 years) and 16 (30.2%) were not at risk (21-35 years). There is an influence between parity, pregnancy distance and age with preeclampsia pregnancies at the Adiarsa Karawang Health Center in 2024 (p-value = 0.046, p-value = 0.004, p-value = 0.026). Pregnant women are expected to increase their knowledge about preeclampsia by actively carrying out examinations through ANC and Posyandu visits so that they can take preventive measures to avoid experiencing preeclampsia during pregnancy. Keywords: Age, Parity, Preeclampsia, Pregnancy Interval  ABSTRAK Menurut data World Health Organization (WHO) tahun 2020 diperkirakan setiap hari terdapat 934 kasus preeklampsia terjadi di seluruh dunia. Sekitar 342.000 ibu hamil merasakan preeklampsia. Menurut study pendahuluan di Puskesmas Adiarsa Karawang diperoleh data kasus preeklampsia pada tahun 2022 sebesar 14,57 %, tahun 2023 sebesar 10,0%. Penelitian ini bertujuan untuk mengetahui pengaruh paritas, jarak kehamilan, dan usia ibu pada kehamilan dengan preeklamsia di Puskesmas Adiarsa Karawang.. Jenis penelitian kuantitatif, rancangan penelitian survei analitik dengan pendekatan cross sectional telah dilakukan di Puskesmas Adiarsa Kabupaten karawang bulan Juni-Juli 2024. Populasi dalam penelitian ini adalah seluruh ibu hamil yang merasakan preeklampsia yang total 110 orang.Sample dalam penelitian ini total 53 dengan teknik sampling yang dipakai secara Purposive Sampling. pengambilan data menggunakan data sekunder yang diambil dari catatan register pasien. Analisis data secara univariat (distribusi frekuensi) dan bivariat (chi square). Diketahui Dari 53 Ibu hamil di Puskesmas Adiarsa Karawang Tahun 2024 total 39  (73.6%) merasakan preeklampsia dan 14 (26.4%)  tidak merasakan preklamsia. 42 (79.2%) dengan paritas berisiko (≥ 4) dan 11 (20.8%) dengan paritas tidak berisiko. 37 (69.8%) dengan jarak kehamilan berisiko (≤ 2 tahun) dan 11 (20.8%) dengan jarak kehamilan tidak berisiko. 37 (69.8%) dengan usia berisiko (≤ 20-≥ 35  tahun) dan 16 (30.2%) dengan usia tidak berisiko (21-35 tahun). Ada pengaruh terkait paritas, jarak kehamilan dan usia dengan kehamilan preeklamsia di Puskesmas Adiarsa Karawang tahun 2024 (p-value = 0,046, p-value = 0,004, p-value = 0,026). Ibu hamil diharapkan dapat menaikkan     pengetahuan     tentang     preeklampsia dengan aktif melaksanakan pemeriksaan melalui kunjungan ANC dan Posyandu sehingga dapat melaksanakan tindakan      pencegahan      agar      tidak      merasakan  adanya  preeklamsia  ketika  hamil. Kata Kunci: Jarak Kehamilan, Paritas, Preeklamsia, Usia